Normative Labels in Two Lexicographic Traditions: A Slovene–English Case Study - Vrbinc, Marjeta; Šipka, Danko; Vrbinc, Alenka (Lexikos, 2020)
This article presents and discusses the findings of a study conducted with the users of Slovene and American monolingual dictionaries. The aim was to investigate how native speakers of Slovene and American English interpret select normative labels in monolingual dictionaries. The data were obtained by questionnaires developed to elicit monolingual dictionary users’ attitudes toward normative labels and the effects the labels have on dictionary users. The results show that a higher level of prescriptivism in the Slovene linguistic culture is reflected in the Slovene respondents’ perception of the labels (for example, a stronger effect of the normative labels, a higher approval for the claim about usefulness of the labels, a considerably lower general level of acceptance for the standard language) when compared with the American respondents’ perception, since the American linguistic culture tends to be more descriptive. However, users often seek answers to their linguistic questions in dictionaries, which means that they expect at least a certain degree of normativity. Therefore, a balance between descriptive and prescriptive approaches should be found, since both of them affect the users.